Analyzing the thematic-integrative content, the scientific approach, and the authentic assessment in the theme 1 textbook for grade II students of elementary schools - Putri Zudhah Ferryka (Jurnal Prima Edukasia, 2017)
This study aimed at describing the integrative-thematic content, the scientific approach, and the authentic assessment in the 2013 Curriculum Theme 1 Textbook Peaceful Life for the Grade II Students of Elementary School. This study was a content analysis research using a qualitative approach. The subject in this study was 2013 Curriculum Theme 1 Textbook Peaceful Life for the Grade II Students of Elementary School. Then, the objects of this study were integrative-thematic content, scientific approach, and authentic assessment. The data analysis that the researcher employed consisted of data gathering, sample selecting, data recording, data reducing, conclusion drawing, and narrating. The results of the study show that: (1) most of the integrative-thematic contents in the 2013 Curriculum Theme 1 Textbook Peaceful Life for the Grade II Students of Elementary School have been in accordance with the indicators but the author still make some errors within the contents; (2) the scientific approach that has been embedded into the textbook includes various activities that direct the students to interact with their environment in establishing their own knowledge; and (3) the authentic assessment has been in accordance with the indicators.